2015
DOI: 10.1016/j.jbankfin.2014.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of European retail payments

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 57 publications
2
14
0
Order By: Relevance
“…The results by Hasan et al (2012Hasan et al ( , 2013 suggests that migration from paper to electronic retail payments has a positive impact on the banking sector performance and the real economy in the EU. In contrast, Schmiedel et al 2012 Within the Eurozone, electronic forms of payments are popular, and increasingly so in Finland, Netherlands, Estonia, Luxembourg, Germany, and Austria (see Martikainen et al 2013 and Figure 1). In contrast, they remain particularly little used in Greece, Italy, Malta, and Cyprus.…”
Section: Retail Payment Infrastructure and The Macroeconomymentioning
confidence: 98%
See 2 more Smart Citations
“…The results by Hasan et al (2012Hasan et al ( , 2013 suggests that migration from paper to electronic retail payments has a positive impact on the banking sector performance and the real economy in the EU. In contrast, Schmiedel et al 2012 Within the Eurozone, electronic forms of payments are popular, and increasingly so in Finland, Netherlands, Estonia, Luxembourg, Germany, and Austria (see Martikainen et al 2013 and Figure 1). In contrast, they remain particularly little used in Greece, Italy, Malta, and Cyprus.…”
Section: Retail Payment Infrastructure and The Macroeconomymentioning
confidence: 98%
“…According to the data of Martikainen et al (2013) this is because of popularity of cash payments in these countries. 1 As argued by Hasan and Takalo (2014), Figure 1 suggests a correlation between payment habits and recent economic fortunes, which we try to capture in Figure 2.…”
Section: Retail Payment Infrastructure and The Macroeconomymentioning
confidence: 99%
See 1 more Smart Citation
“…The authors obtained empirical evidence of a substitution effect between cards and cheques in the volume and value of transactions with cheques. Deungoue (2008) and Martikainen et al (2015), while focusing their analysis on the convergence of payment behaviour in European countries (for the periods from 1990 to 2002 and 1995 to 2001, respectively), put forward some possible reasons for the differences in payments with cheques. In both cases, the results suggested that payments with cheques were not converging in the EU.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, consumption through on-line channels of both goods and services is increasing within the European Union (EU), especially across borders. More consumers have access to the Internet, shipping costs are decreasing and payment services are converging across countries (Marcus and Petropoulos, 2016;Cardona and Duch-Brown, 2016;Martikainen et al, 2015). Accurate estimates of cross-border on-line consumption are of increasing importance for adequately reporting on national accounts by national statistical institutes.…”
Section: Introductionmentioning
confidence: 99%